The Influence of Critical and Creative Thinking of Elementary School Students of Kuripan Kidul 03 on the Material of Energy Changes: Analysis of the Role of Gender and Age - Aprilia Ariestiani Wijayanti; Subuh Anggoro (Proceedings Series on Social Sciences & Humanities, 2025)
This study investigates the relationship between critical thinking and creativity among elementary school students, considering the influence of age and gender. A quantitative correlational approach was employed, involving 167 students aged 9-13 years. Non-parametric statistical methods, including Spearman's correlation, Kruskal-Wallis H test, and Mann-Whitney U test, were used due to the non-normal distribution of the data. The results revealed a strong positive correlation between critical thinking and creativity (? = 0.902, p = 0.023). Creativity significantly differed by age (H = 1.756; p = 0.041), with the 9-10 year age group exhibiting the highest creativity scores. A significant gender difference was also found in creativity (p = 0.029), with males scoring higher on average. Conversely, females exhibited slightly higher critical thinking scores. The study concludes that critical thinking and creativity are closely related in elementary students, with age and gender playing a significant role. Educational interventions should aim to foster both skills, considering the decline in creativity with age and the observed gender differences.